Analisis Kepuasan, Kesenjangan Kinerja dan Kepentingan Pelayanan Humas di Cibinong Science Center - Botanical Garden LIPI - Susanti, Ika (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2020)
LIPI Public Relations is one of the support services functions that provide scientific services to researchers in terms of cooperation, public information, media and inter-institutions relations, and facilitating the socialization of science and technology. Reorganization causes changes in the function of public relations services from work units to regions, so it is necessary to analyze the satisfaction, performance and interest gaps of public relations services in the Cibinong Science Center-Botanical Garden LIPI. This study used a quantitative method approach with qualitative data as a support. Data was analyzed from two instruments, i.e. Community Satisfaction Index (IKM) and Importance Performance Analysis (IPA). Among four PR service functions, three of them (cooperation, public information, media and inter-institutional relations) were perceived as working properly, meanwhile for facilitating the socialization of science and technology was not good. Officer behavior indicator was good, thus needed to be maintained. IKM’s indicators, such as: service requirements, procedures, completion time, product specifications, competence of officers, and complaints handling were not good enough, so that it became a priority for improvement. Moreover, the cost and infrastructure indicators could be ignored. Research suggested that the implementation of procedures was a priority for short-term improvement. Furthermore, development of product specifications and enhancing the competence of officers were short-term to medium-term improvement priorities.